Efficacy of levetiracetam for reducing rolandic discharges in comparison with carbamazepine and valproate sodium in rolandic epilepsy. (November 2018) - Kanemura, Hideaki; Sano, Fumikazu; Ohyama, Tetsuo; Aihara, Masao
Highlights: We compared the efficacy of CBZ/VPA and LEV for reducing RD in children with RE. 12.5% of CBZ patients and 51.2% of VPA patients were considered responders. 71.4% of 35 patients treated with LEV were considered responders. Durations before EEG response in CBZ/VPA/LEV groups were 36.3/23.1/14.7 months. EEG response was achieved more rapidly with LEV than with CBZ/VPA. Abstract: Purpose: The main purpose of this study was to compare the efficacy of levetiracetam (LEV) with the older antiepileptic drugs (AEDs) for preventing atypical evolution in children with Rolandic epilepsy (RE). Accordingly, the present study compared the efficacy of older AEDs (carbamazepine (CBZ) and valproate sodium (VPA)) with LEV in reducing rolandic discharges (RDs) on interictal electroencephalogram (EEG) in children with RE. Methods: Patients in this heterogenous study were subdivided into CBZ, VPA and LEV groups in accordance with the initial monotherapy. The CBZ and VPA groups were studied retrospectively, but the LEV group was studied prospectively. Appearances of discharges were counted and these rates were computed. In comparison with the baseline RD frequency, EEG response to AED treatment was classified such as complete disappearance and response (≥50% reduction in RD frequency). The time taken to attain complete disappearance or response in EEG responders was assessed for each AED treatment group. Results: Responders comprised 10 (11.2%) of the 89 patients treated with CBZ, 41 (56.2%) of the 73 patients with VPA, and 25 (71.4%) of the 35 patients with LEV. Mean interval to achievement of EEG response in the CBZ, VPA, and LEV groups were 36.3, 23.1, and 14.7 months, respectively. EEG response was achieved significantly more rapidly with LEV than with CBZ (p < 0.001) or VPA (p < 0.005). Seizure control was not significantly different in all 3 investigated drugs. Conclusions: LEV seems to be superior to CBZ and VPA in its ability to suppress RDs in children with RE.